Dokumente. Journalistenverband Jugoslaviens. Medunarodna politika
Engl. ed.: Documents. Federation of Yougoslav journalist (ZO 30609) - French ed.: Documents. L'Union des journalistes de Yougoslavie (ZO 30609).